2006
DOI: 10.1111/j.1469-0691.2005.01337.x
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis jirovecii colonisation in patients with interstitial lung disease

Abstract: A prospective study was conducted to determine the prevalence of colonisation by Pneumocystis jirovecii in 80 consecutive patients who required bronchoscopy and bronchoalveolar lavage (BAL) following suspicion of interstitial lung disease (ILD). The mtLSU rRNA gene of P. jirovecii was identified by nested PCR in BAL samples. Patients with ILDs were divided into three groups: group A comprised those with idiopathic interstitial pneumonias; group B comprised those with sarcoidosis; and group C comprised those wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 31 publications
1
66
0
8
Order By: Relevance
“…Widespread use of PcP chemoprophylaxis and Highly Active Antiretroviral Therapy (HAART) have 220 Mise au point Parasite, 2010, 17, 219-232 inflammatory bowel disease (Sepkowitz 2002;Kaneko et al, 2006;Poppers & Scherl, 2008). This organism has also been isolated from immunocompetent persons and also patients with lung tissue damage caused by different clinical conditions are at increased risk of P. jirovecii colonization (Pifer et al, 1978;Matos et al, 2003;Montes-Cano et al, 2004;Medrano et al, 2005;Matos et al, 2006;Vidal et al, 2006;Esteves et al, 2008). Also, in developing regions of the Globe, where most HIVinfected persons reside, there is an increased incidence of PcP since the access to HAART and PcP prophylaxis is still limited (WHO, 2003;French et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Widespread use of PcP chemoprophylaxis and Highly Active Antiretroviral Therapy (HAART) have 220 Mise au point Parasite, 2010, 17, 219-232 inflammatory bowel disease (Sepkowitz 2002;Kaneko et al, 2006;Poppers & Scherl, 2008). This organism has also been isolated from immunocompetent persons and also patients with lung tissue damage caused by different clinical conditions are at increased risk of P. jirovecii colonization (Pifer et al, 1978;Matos et al, 2003;Montes-Cano et al, 2004;Medrano et al, 2005;Matos et al, 2006;Vidal et al, 2006;Esteves et al, 2008). Also, in developing regions of the Globe, where most HIVinfected persons reside, there is an increased incidence of PcP since the access to HAART and PcP prophylaxis is still limited (WHO, 2003;French et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Many terms-colonization, carriage, asymptomatic infection, and subclinical infection-have been used to describe these fi ndings. Studies have shown that persons who have underlying HIV infection or other causes of immunosuppression and those who are not immunosuppressed but have chronic lung disease may often be colonized by P. jirovecii (11)(12)(13). Further hypotheses claim that these groups may play a role in person-to-person transmission and that they may serve as reservoirs for future Pneumocystis infection in other susceptible persons; however, this hypothesis has not been proven.…”
mentioning
confidence: 99%
“…As only those with suspected PCP were tested, this cohort might have been expected to have a higher colonization rate than average. The findings are at odds with reports of colonization rates of 10-46 % in both immune-compromised and immune-competent individuals (Vidal et al, 2006;Wakefield et al, 2003;Maskell et al, 2003;Mori et al, 2009). However, some of these results were based on nested protocols, which often suffer from poor specificity.…”
Section: Discussionmentioning
confidence: 58%
“…Additionally, its detection in hospital air samples up to 8 m from patients with confirmed infection also supports transmission from an infected patient (Choukri et al, 2010). Asymptomatic colonization is thought to be relatively common (Maskell et al, 2003;Wakefield et al, 2003;Vidal et al, 2006) and can progress to overt infection when a patient's immune status deteriorates (Mori et al, 2009). Co-attendance with other immune-compromised patients in health-care settings may, therefore, be a risk factor for colonization and a later overt infectious episode.…”
Section: Introductionmentioning
confidence: 89%